2021
DOI: 10.1177/10892532211041320
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Pain After Cardiac Surgery: Prevention and Management

Abstract: Persistent postoperative pain (PPP) after cardiac surgery is a significant complication that negatively affects patient quality of life and increases health care system burden. However, there are no standards or guidelines to inform how to mitigate these effects. Therefore, in this review, we will discuss strategies to prevent and manage PPP after cardiac surgery. Adequate perioperative analgesia may prove instrumental in the prevention of PPP. Although opioids have historically been the primary analgesic appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 107 publications
0
14
0
2
Order By: Relevance
“…minimize the possibility of persistent chronic pain following cardiac surgery (46,47) but could also reduce the risk of postoperative delirium, which has been identified as a potential sequela of acute pain (48,49) possibly associated with long-term cognitive decline (50). Hence, our findings suggested that incorporation of ITM into the standard pain management strategy may be recommended for this patient population.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…minimize the possibility of persistent chronic pain following cardiac surgery (46,47) but could also reduce the risk of postoperative delirium, which has been identified as a potential sequela of acute pain (48,49) possibly associated with long-term cognitive decline (50). Hence, our findings suggested that incorporation of ITM into the standard pain management strategy may be recommended for this patient population.…”
Section: Discussionmentioning
confidence: 78%
“…Despite the lack of a significant beneficial impact of ITM on mortality or the incidence of myocardial infarction following cardiac surgery from pooled evidence ( 8 , 45 ), optimization of acute pain management with ITM not only may enhance postoperative recovery and minimize the possibility of persistent chronic pain following cardiac surgery ( 46 , 47 ) but could also reduce the risk of postoperative delirium, which has been identified as a potential sequela of acute pain ( 48 , 49 ) possibly associated with long-term cognitive decline ( 50 ). Hence, our findings suggested that incorporation of ITM into the standard pain management strategy may be recommended for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly controlled PP has been shown to increase the risk of pulmonary, cardiovascular, and endocrine complications, long LOS, and chronic pain [ 26 ]. Beyond suffering, pain affects post-operative rehabilitation, resulting in functional disability that prevents return to normal work and life [ 27 ]. Considering that high-dose opioid therapy is associated with prolonged intubation and ventilator-associated pneumonia, which may lead to a longer ICU stay and higher mortality [ 28 ], we adopted a multimodal analgesia strategy with SAPB as the main intervention.…”
Section: Discussionmentioning
confidence: 99%
“… Post-operative pain management: Abundant data have suggested that inadequate postoperative pain control increases morbidity and mortality, and a significant proportion of patients who report severe acute pain will end up suffering from chronic postsurgical pain [ 27 , 42 ]. Despite the small incision in TTCS, postoperative pain management remains very important.…”
Section: Anesthesia Managementmentioning
confidence: 99%
“…5 While the etiology of chronic pain after cardiac surgery is multifactorial, several specific risk factors have been identified. 6,7 These include younger age, female sex, baseline chronic pain, surgical duration, and acute postoperative pain. 2 However, most of these previous studies were insufficiently powered to employ multivariable modeling techniques, and many did not evaluate modifiable perioperative factors.…”
mentioning
confidence: 99%